Concept of Grip Assistive Braking on Four Wheelers - David Jebaraj B; Sharath Prasanna R; Karthikeyan V; Maheshwar D (International Journal of Engineering and Management Research, 2020)
Braking systems in all the segments of vehicles seems to be one of the most crucial developing systems. Many research and developments are carried out in terms of braking of a vehicle in order to enhance the braking efficiency and reduction in stopping distance. This article depicts the concept of assistive braking on four wheelers where we elaborately describe the Braking distance, Thinking distance and Stopping distance after which our concept of braking is proposed with all the technical aspects along with the various components and its efficiency in our real time use. This research article mainly focuses on technical aspects that aim to reduce the reaction time and reflex actions of the driver which in turn is used as a factor to reduce the stopping distance of the vehicle. Various types of biological reactions by a human are observed and then a particular muscular reaction is chosen as a source of intimation for our braking system. When an object is spotted by the driver, the reflex action takes place via a receptor, sensory neurons, spinal cord and from where the muscular reaction takes place. A unique steering with an array of grip sensors is designed and incorporated also with various functions of the vehicle but for this instance, we mainly focus on braking assistance of the vehicle. Thus the unique steering wheel plays the role of connection between vehicle and the driver.